A Feasibility Study of a Music Enrichment Program on Relative Reinforcing Value of Food and Home Environmental Enrichment among Families of Low Socioeconomic Status - Kai-Ling Kong; Amy R. Smith; Brenda Salley; Deanna Hanson-Abromeit; Hideko Engel; Catherine A. Serwatka (MDPI AG, 2024)
Background: Emerging evidence suggests that low socioeconomic status (SES) home environments may play a role by promoting excess energy intake through a lack of access to non-food reinforcers. Because of the deleterious effects of SES-related disparities on child health and development, feasible and culturally acceptable interventions are urgently needed. Community-based music enrichment programs may be an ideal intervention strategy. Methods: In collaboration with a local non-profit organization and music studio, we conducted a pilot randomized controlled trial to assess the effects of a music enrichment program versus a play date control in a group of 9-24-month-old healthy infants (N = 16). The study was conducted in accordance with the Declaration of Helsinki and approved by the Institutional Review Board of Children's Mercy Hospital Kansas City. This study is registered with clinicaltrials.gov (NCT05868811). Results: Overall, we found some intervention effects on the relative reinforcing value of food (RRVfood) and the home environmental enrichment measures (i.e., increased music use at home and the home language environment). Our intervention demonstrated large effects on the increased use of music at home. We did not find significant group differences in the RRVfood and home language environment, but some of the effect sizes were medium-to-large. Results also suggest that our intervention is feasible and acceptable. Parent feedback indicated that the intervention was well-liked and that the steps we took to help reduce barriers worked. Conclusions: Music enrichment programs may be a high-impact, low-cost strategy to address socioeconomic disparities.